Islamic Law, International Humanitarian Law, and Indonesia’s Diplomacy: A Constructivist Reading of Prabowo’s UNGA Speech on Gaza, 2025 - Fuhaidah, Ulya; Wijaya, Roma (Islamic Law and Social Issues in Society, 2026)
Studies on the normative overlap between Islamic law and International Humanitarian Law (IHL) have consistently shown how both traditions converge in their commitment to human dignity. What has received far less attention is how this convergence travels into the practice of state diplomacy and shapes the construction of foreign policy identity. This article takes up that question by reading President Prabowo Subianto’s 2025 address to the UN General Assembly as a diplomatic text through which the convergence between maqāṣid al-sharīʿah and IHL is articulated and publicly justified in Indonesia’s response to the Gaza crisis. The central argument is that Prabowo’s speech frames Indonesian foreign policy as value-based diplomacy anchored in Islamic ethics and in widely recognized humanitarian norms. Using qualitative content analysis within a constructivist framework, the study treats maqāṣid al-sharīʿah not only as an ethical doctrine but as a normative resource that informs identity construction and shapes diplomatic conduct. The analysis shows that Prabowo’s speech reflects an Indonesian foreign policy grounded in justice and humanity and draws the protection of life (ḥifẓ al-nafs), justice (ʿadl), and global solidarity into a single ethical vocabulary that projects Islamic values into modern diplomacy. Read together, these findings suggest that Indonesia’s diplomacy operates as a site of cross-civilizational moral articulation, linking Islamic ethics with universal humanitarian standards while contributing to a more inclusive and morally grounded diplomatic paradigm. The article thus contributes to constructivist international relations scholarship by showing how religious normative frameworks can serve as intersubjective sources of international norms that shape state identity and diplomatic behavior. On that basis, it proposes a value-based humanitarian diplomacy model that bridges Islamic ethics and contemporary humanitarian law in global political practice.